2010
DOI: 10.1590/s0103-84782010005000081
|View full text |Cite
|
Sign up to set email alerts
|

Adventitious rooting of auxin-treated Lavandula dentata cuttings

Abstract: Lavandula species may be propagated by seeds. However, plants will present expressive variation both in size and essential oil content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Rooting of stem cutting is widely used in horticulture for the propagation of aromatic and medicinal plants, however poor rooting is often observed (Kasem and El-baset, 2014). In order to overcome this problem synthetic auxins are often applied at stimulating the adventitious root formation on cuttings (Bona et al, 2010), however due to the continuous increase of environmental footprint it is urgent to find eco-friendly alternatives. Although several studies have reported the beneficial effect of BE and PGPR inoculation in several economically-important crops, like maize (Pereira and Castro, 2014a), carrot and potatoes (Surette et al, 2003), little information is available for aromatic and medicinal plants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rooting of stem cutting is widely used in horticulture for the propagation of aromatic and medicinal plants, however poor rooting is often observed (Kasem and El-baset, 2014). In order to overcome this problem synthetic auxins are often applied at stimulating the adventitious root formation on cuttings (Bona et al, 2010), however due to the continuous increase of environmental footprint it is urgent to find eco-friendly alternatives. Although several studies have reported the beneficial effect of BE and PGPR inoculation in several economically-important crops, like maize (Pereira and Castro, 2014a), carrot and potatoes (Surette et al, 2003), little information is available for aromatic and medicinal plants.…”
Section: Resultsmentioning
confidence: 99%
“…However, the poor rooting capacity of cuttings is often observed. In order to overcome this problem, plant growth regulators like the indole-3-butyric acid (IBA) and indole-3-acetic acid (IAA) are commonly used and showed to be efficient in increasing the adventitious root formation and the rooting capacity of cuttings (Bona et al, 2010;Kasem and El-baset, 2014). However, chemical application raises environmental concerns and increase production costs thus the use of sustainable practices in the production of medicinal and aromatic plants is imperative.…”
Section: Introductionmentioning
confidence: 99%
“…Lavandula dentata L. is popularly known as lavender and it is a medicinal plant used in the traditional medicine as an antidiabetic, antispasmodic, anti-hypertensive against common flu and renal colic. It is also used in the ornamentation and as a melliferous plant [8][9][10][11][12][13][14] . Two problems are linked with medicinal and herbal drug plants, the adulteration and tampering 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Rooting percentage was considered good, ranging from 80% to 100%, with 20 roots, 10 to 12 cm-long per cutting, in average (Table 2). Such great rooting percentage may be compared to percentages obtained by Bona et al (2010) in L. dentata, a Lavandula species which was considered easy to root. Auxin did not influence rooting on G2 either, which presented approximately 50% rooting, with five roots, 6-7 cm-long per cutting, in average (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Herein, similarly to results obtained by Blythe et al (2003) on cuttings of Hedera helix, although auxin was not essential for rooting, root percentage and length were greater when treated with IBA. Bona et al (2010) observed that percentage of roots of L. dentata increased with IBA application and a quadratic regression was obtained for root number, being 2000 mg L -1 considered the best IBA concentration. Table 3.…”
Section: )mentioning
confidence: 90%